2012
DOI: 10.1111/j.1476-5381.2012.01917.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the MMP system, adrenoceptors and phosphoprotein phosphatases

Abstract: The MMPs and their inhibitors [tissue inhibitor of MMPs (TIMPs) ] form the mainstay of extracellular matrix homeostasis. They are expressed in response to numerous stimuli including cytokines and GPCR activation. This review highlights the importance of adrenoceptors and phosphoprotein phosphatases (PPP) in regulating MMPs in the cardiovascular system, which may help explain some of the beneficial effects of targeting the adrenoceptor system in tissue remodelling and will establish emerging crosstalk between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 181 publications
(205 reference statements)
1
20
0
2
Order By: Relevance
“…However, this suggestion may not be true in animal models of disease conditions. Matrix metalloproteinases, particularly MMP-2, are known to affect b 1 -and b 2 -adrenoreceptors [21][22][23][24]. The significant attenuation in dobutamine-induced reduction in SVRI after the infusion of rhMMP-2 is consistent with impaired b 2 -adrenoreceptors-mediated vasodilation possibly resulting of enhanced MMP-2 activity.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…However, this suggestion may not be true in animal models of disease conditions. Matrix metalloproteinases, particularly MMP-2, are known to affect b 1 -and b 2 -adrenoreceptors [21][22][23][24]. The significant attenuation in dobutamine-induced reduction in SVRI after the infusion of rhMMP-2 is consistent with impaired b 2 -adrenoreceptors-mediated vasodilation possibly resulting of enhanced MMP-2 activity.…”
Section: Discussionsupporting
confidence: 57%
“…Recent studies indicate that MMPs, including MMP-2, are involved in proteolytic cleavage of b 1 -and b 2 -adrenoreceptors [21]. Rodrigues et al [22] demonstrated that the labelling density of the extracellular domain of b 2 -adrenergic receptor in aortic endothelial cells from Wistar rats was reduced after treatment with plasma of spontaneously hypertensive rats with increased MMPs levels, thus indicating cleavage of b 2 -adrenergic receptors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Other than TIMPs (reviewed in Rietz and Spiers 45 and Brew and Nagase 46 ), little is known about endogenous inhibitors of MMP-9. We reported previously that inflammatory factors such as cytokines and PGE2 induce DC-derived MMP-9 and migration and that endogenous agents such as IFN-␤ inhibit DC migration partially through the transcriptional suppression of Mmp9.…”
Section: Discussionmentioning
confidence: 99%
“…Generalmente, las proenzimas son activadas en situaciones donde sea requerida exclusivamente la degradación de la MEC. Algunas citocinas como interleucina 4 y interleucina 13 son antiinflamatorias y por lo tanto, pueden ejercer funciones inhibitorias de las MMPs, principalmente de su forma latente 48 .…”
Section: Mmps Durante La Cicatrizaciónunclassified